The Role of Immunophenotyping in the Diagnosis of Acute Leukemia: A Narrative Literature Review - Rivani Sintia Suratman; Rudy Afriant; Drajad Priyono; Raveinal; Fauzar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Leukemia is the expansion of leukocyte cells in the bone marrow, which results in an increase in the number of leukocyte cells in the blood circulation and abnormal cell proliferation in the lymphatic tissue. The diagnosis of leukemia is established based on anamnesis, physical examination, and laboratory and confirmed by supporting examinations such as bone marrow aspiration to immunophenotyping. This literature review aimed to describe the role of immunophenotyping in the diagnosis of acute leukemia. The working process of immunophenotyping consists of a group of cells stained with a fluorochrome-conjugated antibody as a dye that is targeted to antigens on the cell surface. Most of these antigens are assigned a cluster of differentiation (CD) numbers. In conclusion, immunophenotyping analysis using multiparameter flow cytometry is an essential tool in detecting leukemia. Immunophenotyping examination is very useful for determining the diagnosis of leukemia. Targeted therapy is one of the modalities of leukemia therapy that is selective for certain cells that can be given based on the results of immunophenotyping.